The experience of physiological and psychosocial alcohol‐related harms across adolescence and its association with alcohol use disorder in early adulthood: A prospective cohort study. (18th December 2021) - Yuen, Wing See; Bruno, Raimondo; Chan, Gary C. K.; McCambridge, Jim; Slade, Tim; Clare, Philip J.; Aiken, Alexandra; Kypri, Kypros; Hutchinson, Delyse; McBride, Nyanda; Boland, Veronica; Upton, Emily; et al.
Abstract: Background: Different forms of alcohol‐related harm (e.g., hangovers, fighting) may confer differential risk of clinically relevant alcohol problems. We examine: (i) patterns of transition in experiencing alcohol‐related harms across adolescence; (ii) whether factors in early adolescence predict transition patterns; and (iii) whether transition patterns predict later alcohol use disorder (AUD) symptoms. Methods: We used a longitudinal Australian cohort ( n = 1828) to model latent class transition patterns of alcohol‐related harms across three timepoints ( M age = 13.9, 16.8, 18.8 years). Regression models assessed whether child, peer, and parent factors in early adolescence ( M age = 12.9) predicted harms transition patterns and whether these patterns predicted AUD symptoms in early adulthood ( M age = 19.8). Results: Five transition patterns characterized most of the cohort ( n ≈ 1609, 88.0%): (i) minimal harms ( n ≈ 381, 20.8%); (ii) late physiological harms ( n ≈ 702, 38.4%); (iii) early physiological harms ( n ≈ 226, 12.4%); (iv) late all harms ( n ≈ 131, 7.2%); and (v) gradual all harms ( n ≈ 169, 9.2%). With late physiological harms as the reference, females had increased risk of experiencing early physiological harms (relative risk [RR]: 2.15; 99.5% CI: 1.19, 3.90). Late all harms (RR: 1.71; CI: 1.19, 2.47) and gradual all harms (RR: 1.84; CI: 1.37, 2.47) were each associated with increased odds of meeting criteria for AUD, even when patterns of alcohol consumption are considered. Conclusions: Adolescents display heterogeneous transition patterns across physiological and psychosocial alcohol‐related harms. Females are at greater risk of experiencing early physiological harms. Experience of both physiological and psychosocial harms in late adolescence is an important and potentially modifiable precursor to clinically relevant alcohol problems in early adulthood. Abstract : Different forms of alcohol‐related harm may confer differential risks of clinically relevant alcohol problems. Using latent transition analyses, our study found that patterns of transition across these forms of alcohol‐related harm vary among adolescents as they age. Whilst the majority experienced only physiological harms, such as blackouts, around 20% of the sample also experienced psychosocial harms such as interpersonal conflict. Females were at greater risk of physiological alcohol‐related harms. Late adolescent psychosocial harm predicted adulthood alcohol use disorder symptoms.